2020
DOI: 10.1108/ijse-05-2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

Does mobile money promote financial inclusion in Eswatini?

Abstract: PurposeMobile money, a service permitting monetary value to be digitally stored in a mobile phone and transacted to others through text messaging, is increasingly becoming available in several African countries including Eswatini. This study examines the factors associated with mobile money usage and the extent to which mobile money accelerates financial inclusion in Eswatini. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The results confirm the significant role of financial inclusion and mobile money use in alleviating poverty and increasing individuals' well-being. Myeni et al (2020) examined how mobile banking promotes financial inclusion based on data from the "FinScope" consumption survey conducted in Eswatini, 2014 edition. The authors found that having a high educational attainment, entrepreneurial skills and living in urban areas are the determinants of mobile money use.…”
Section: Financial Inclusion and Mobile Bankingmentioning
confidence: 99%
“…The results confirm the significant role of financial inclusion and mobile money use in alleviating poverty and increasing individuals' well-being. Myeni et al (2020) examined how mobile banking promotes financial inclusion based on data from the "FinScope" consumption survey conducted in Eswatini, 2014 edition. The authors found that having a high educational attainment, entrepreneurial skills and living in urban areas are the determinants of mobile money use.…”
Section: Financial Inclusion and Mobile Bankingmentioning
confidence: 99%
“…This system offers various services to users, such as making payments with the mobile phone, sending and receiving money between users (and non-users), withdrawing cash at ATMs. G-Cash in the Philippines (Pelletier et al, 2020), Nequi in Colombia (Agidi, 2018), Swazi MTN in Eswatini (Myeni et al, 2020), WIZZIT and MTN Mobile Money in South Africa, and CELPAY in Zambia (Andrianaivo and Kpodar, 2012) are also considered successful implementations of mobile money in low-income countries. However, it is important to highlight the fact that while similar m-payment systems and technology initiatives can be found in various developing countries, only a few have achieved high adoption rates capable of supporting the scale required for extensive use Potnis et al (2020).…”
Section: Bottom Of the Pyramidmentioning
confidence: 99%
“…There is a convergence between banking and mobile money channels (Myeni et al 2020). Partnerships that bring together banks and MNOs carry advantages for both categories of partners and allows for both partners to benefit from the strengths of each.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that drive financial inclusion arising from the adoption and usage of mobile money include age, digital literacy and availability of associated services such as phone credit recharge, education, and income (Amoah et al 2020). Further, entrepreneurship, gender, living in urban or rural areas all positively influence the probability to adopt and use mobile money (Myeni et al 2020). Also, the density of registered mobile money agents per 100,000 adults led to an increase in the total number of people using the financial services per 100,000 adults in Sub-Sahara Africa and the relationship between the registered mobile money agents per 100,000 adults and the total number of people using financial services was proven to be significant (Nyimbiri 2021).…”
Section: Banking Mobile Money and Implications For Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation